Multidimensional Impact Analysis of Corrupt Practices in Nickel Mining on Sustainable Development in North Maluku - Deni, Aji; Kristanto, Budi (Jurnal Manajemen Pelayanan Publik, 2024)
This study examines the multifaceted impacts of corrupt practices in the nickel mining industry in North Maluku. Corrupt practices in the mining sector remain a major issue, leading to various problems such as agrarian conflicts, environmental degradation, economic inequality, and health issues. Numerous studies indicate that these corrupt practices stem from the same scheme such as excessive exploitation of natural resources due to abuse of power by political elites at both local and national levels, who collude with entrepreneurs to commit maladministration mining permits, issuing overlapping licenses, and seizing land. This qualitative research collects data through interviews, field observations, and documentation. Data analysis includes reduction, presentation, and conclusion drawing. The study reveals that the nickel mining business in North Maluku still contradicts the principles of sustainable environmental conservation, human rights, and neglects the living rights of local communities. Therefore, To mitigate the impacts of mining exploitation, entrepreneurs need stronger corporate social responsibility, effective government policies, building collaborative partnerships, eliminating institutional corruption, and prioritizing a holistic and integrated approach to surrounding communities through social and economic development programs that emphasize community welfare and improve the equality of the environment, community, health, and local economy.